TEACHING ENGLISH YOUNG LEARNERS - Axrorova Amira Aminovna (Western European Studies, 2024)
The article examines some methods of teaching English to young students and gives a broad definition of these methods, explaining why they are more convenient in teaching the language.
Keywords: individual methods; popular methods; joyful vocabulary